CAl4Mg0/−: Global Minima with a Planar Tetracoordinate Carbon Atom - Nisha Job; Maya Khatun; Krishnan Thirumoorthy; Sasanka Sankhar Reddy CH; Vijayanand Chandrasekaran; Anakuthil Anoop; Venkatesan S. Thimmakondu (Atoms, 2021)
Isomers of CAl4Mg and CAl4Mg− have been theoretically characterized for the first time. The most stable isomer for both the neutral and anion contain a planar tetracoordinate carbon (ptC) atom. Unlike the isovalent CAl4Be case, which contains a planar pentacoordinate carbon atom as the global minimum geometry, replacing beryllium with magnesium makes the ptC isomer the global minimum due to increased ionic radii of magnesium. However, it is relatively easier to conduct experimental studies for CAl4Mg0/− as beryllium is toxic. While the neutral molecule containing the ptC atom follows the 18 valence electron rule, the anion breaks the rule with 19 valence electrons. The electron affinity of CAl4Mg is in the range of 1.96–2.05 eV. Both the global minima exhibit π/σ double aromaticity. Ab initio molecular dynamics simulations were carried out for both the global minima at 298 K for 10 ps to confirm their kinetic stability.